2021
DOI: 10.3390/cancers13092230
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performances of the ACR-TIRADS System in Thyroid Nodules Triage: A Prospective Single Center Study

Abstract: Ultrasound scores are used to determine whether thyroid nodules should undergo Fine Needle Aspiration (FNA) or simple clinical follow-up. Different scores have been proposed for this task, with the American College of Radiology (ACR) TIRADS system being one of the most widely used. This study evaluates its ability in triaging thyroid nodules deserving FNA on a large prospective monocentric Italian case series of 493 thyroid nodules from 448 subjects. In ACR 1–2, cytology never prompted a surgical indication. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Various studies have shown the good performance of ACR-TIRADS in selecting thyroid nodules deserving FNA, stressing its high "rule-out" role, as confirmed by our group here and previous experience [1,6,8,[16][17][18]. In the present work, the ACR and EU-TIRADS systems recommended FNA in 46.5% (223/480) and 51.9% (249/480) of the nodules, respectively.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Various studies have shown the good performance of ACR-TIRADS in selecting thyroid nodules deserving FNA, stressing its high "rule-out" role, as confirmed by our group here and previous experience [1,6,8,[16][17][18]. In the present work, the ACR and EU-TIRADS systems recommended FNA in 46.5% (223/480) and 51.9% (249/480) of the nodules, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…However, the only feature with a significant influence on diagnostic accuracy was the increased vascularization of the nodules, which is not taken into account by both the ACR and EU-TIRADS systems. Other recent studies investigated the impact of different dimensional cutoffs, e.g., ≤2 and >2 cm, on the final performances of the available US systems, showing a range of values quite close to the ones obtained in the present cohort with the ACR and EU-TIRADS systems [8,29]. An innovative approach was proposed in 2017 by He et al, creating a new algorithm that significantly increased the predictive performance of US features [30].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations